2015
DOI: 10.3109/14756366.2015.1101093
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of amidino-substituted benzimidazole and benzimidazo[1,2-a]quinoline derivatives tested in 2D and 3D cell culture systems

Abstract: Due to a poor clinical predictive power of 2D cell cultures, standard tool for in vitro assays in drug discovery process, there is increasing interest in developing 3D in vitro cell cultures, biologically relevant assay feasible for the development of robust preclinical anti-cancer drug screening platforms. Herein, we tested amidino-substituted benzimidazoles and benzimidazo[1,2-a]quinolines as a small platform for comparison of antitumor activity in 2D and 3D cell culture systems and correlation with structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…Simplistic monolayer cultures have their advantages, but they are often significantly different in gene expression, epigenetics, and cell function compared to native 3D tissues . Also, they often lack cell–cell and cell–matrix interactions, leading to the absence of tissue specific properties. Although animal models are widely used in biomedical research, they fail to faithfully predict human responses in a physiologically relevant manner due to the significant species divergences .…”
Section: Introductionmentioning
confidence: 99%
“…Simplistic monolayer cultures have their advantages, but they are often significantly different in gene expression, epigenetics, and cell function compared to native 3D tissues . Also, they often lack cell–cell and cell–matrix interactions, leading to the absence of tissue specific properties. Although animal models are widely used in biomedical research, they fail to faithfully predict human responses in a physiologically relevant manner due to the significant species divergences .…”
Section: Introductionmentioning
confidence: 99%
“…As standard drugs we tested doxorubicin, docetaxel, vinorelbine and gemcitabine. All cell lines showed increased chemoresistance in 3D cell growth to standard drugs and for some compounds from our platform we have observed significant disagreement indicating that some prominent compounds can be discarded in the early phase of research, while a chance was given to compounds with false positive result (23). We concluded that, as well as in 2D assay, the shift in IC 50 in a 3D cell culture models is not dependent only on the mode of action of the tested compounds, but it is also affected by the cell line sensitivity and (in case of 3D cultures) spheroid stability, and cell line growth have an impact on the cell line sensitivity.…”
Section: Applications Of 3d Cell Culture In Drug Discoverymentioning
confidence: 92%
“…In vivo testing may even be needed to distinguish discrepancies between two separate in vitro study results. In a study regarding the antitumor activity of amidino-substituted benzimidazole and benzimidazo [1, 2-a] quinoline derivatives, the 2D cell cultures used for in vitro testing were found comparable to 3D cell cultures, but significant disagreements in data indicated false positive results, in which in vivo profiling was needed for confirmation [31]. This strengthens the notion that in vitro studies alone, no matter how promising, are not a reliable indicator of a drug's performance which renders the necessity of in vivo studies.…”
Section: The Need For In Vivo Researchmentioning
confidence: 99%